2011
DOI: 10.1038/leu.2011.209
|View full text |Cite
|
Sign up to set email alerts
|

Circulating t(2;5)-positive cells can be detected in cord blood of healthy newborns

Abstract: RK et al. Patterned CpG methylation of silenced B cell gene promoters in classical Hodgkin lymphoma-derived and primary effusion lymphoma cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
(10 reference statements)
0
14
0
1
Order By: Relevance
“…Previously, we have shown that ALCL-propagating cells express a gene signature associated with an ETP in keeping with a presumed thymic origin as described in the current model 32 . Indeed, NPM–ALK transcripts have been detected in 2% of newborn cord blood 33 and expression of NPM–ALK is regulated by the endogenous NPM1 promoter, which drives ubiquitous expression of NPM1 including in thymic progenitors ( Supplementary Fig. 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that ALCL-propagating cells express a gene signature associated with an ETP in keeping with a presumed thymic origin as described in the current model 32 . Indeed, NPM–ALK transcripts have been detected in 2% of newborn cord blood 33 and expression of NPM–ALK is regulated by the endogenous NPM1 promoter, which drives ubiquitous expression of NPM1 including in thymic progenitors ( Supplementary Fig. 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the tumour propagating or cancer stem cell for ALCL identified a gene signature characteristic of an early thymic progenitor within this distinct cellular subset (Moti et al , ). In support of this concept, NPM1‐ALK transcripts were detectable in 2/103 samples of newborn cord blood sampled from an otherwise healthy population (Laurent et al , ). Together these data suggest that the generation of the t(2;5) may be an early event occuring in primitive haemopoietic cells and perhaps requiring a thymic environment or at least T cell‐specific events for transformation although rare ALK+ B cell lymphomas do exist (Laurent et al , ).…”
Section: Phenotype and Cell Of Originmentioning
confidence: 92%
“…Historically, mature T cells were presumed to be the targets for transformation, based on gene expression profiling and the presence of surface markers such as CD4 or CD30, as well as production of cytotoxic proteins such as Granzyme B and Perforin (Benharroch et al, 1998; Eckerle et al, 2009; Swerdlow et al, 2008). However, ALK+ cells are present in stem cell-enriched cord blood, and a study has identified a side population of cells in ALK+ ALCL cell lines and tumors with signatures similar to early thymic progenitors (ETPs), suggesting that transformation of T cells by NPM-ALK might occur early during thymic T cell development (Laurent et al, 2012; Moti et al, 2015). Subsequently, a mechanism has been proposed whereby in a murine mimic of ALK+ ALCL transient expression of a functional TCR is required for thymic emigration of incipient, thymic-resident tumor cells, but the TCR is then downregulated for peripheral lymphomagenesis (Malcolm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%